Manajemen Risiko Proyek Pembangunan Underpass Gatot Subroto Denpasar - I Gusti Agung Istri Mas Pertiwi; Wayan Sri Kristinayanti; I Gede Made Oka Aryawan (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2016)
The developmet of construction projects found many uncertainties that are difficult to predict, so as it is necessary to analyze the risks. Early identification of risks that were identified in this study was 102 to 83 risks and relevant risk. Research using qualitative and quantitative methods with the stage of identifiying the risk of possible risks, risk assessment and risk maping to determine the risks classified as extreme risk, high risk, moderate risk or low risk. Creation of risk maps and the determination of risk category as a reference for decision making risk management measures. 83 shows the results of the relevant risks are risks that are categorized as 25 extreme riks, with the percentage of 44 sourced from project risk, 16% from tecnic risk, 12% from safety risk, 8% from economic and planning, 4% from environtment risk, nature risk and criminal risk. And as 26 high risk, with the percentage of 31 sourced from project risk, 19% from tecnic and environment, 12% from planning risk, 8% from economic risk, 4% from politic risk, human risk and safety risk.